CuO nanoparticles: synthesis and application as an efficient reusable catalyst for the preparation of xanthene substituted 1, 2, 3-triazoles via click chemistry. Issue 35 (26th August 2015) - Iniyavan, P.; Balaji, G.L.; Sarveswari, S.; Vijayakumar, V.
Graphical abstract: Abstract: Copper(II) oxide (CuO) nanoparticles have been found to be an efficient catalyst for 1, 3-dipolar cycloaddition (CuAAC) of aromatic azides and acetylenic xanthenes furnishing the corresponding xanthene substituted triazoles in excellent yields. CuO nanoparticles have been synthesized from copper acetate by simple co-precipitation method and characterized by scanning electron microscope, energy dispersive X-ray analysis, transmission electron microscope, and X-ray diffraction analysis. The salient features of the present protocol are mild reaction conditions, shorter reaction time, reusability of the catalyst, and applicability to a wide range of substrates.